Multimodality imaging assessment of endoleaks post-endovascular aortic repair - Partovi, Sasan; Rengier, Fabian (British journal of radiology, 2018)
Endoleaks are a common complication of endovascular aortic repair (EVAR). As a result, patients require lifelong imaging surveillance following EVAR. In current clinical practice, evaluation for endoleaks is predominantly performed with CT angiography (CTA). Due to the significant cumulative radiation burden associated with repetitive CTA imaging, as well as the repeated administration of nephrotoxic contrast agent, contrast-enhanced ultrasound (CEUS) and magnetic resonance angiography (MRA) have evolved as potential modalities for lifelong surveillance post-EVAR. In this paper, multimodality imaging, including CTA, CEUS and MRA, for the surveillance of endoleaks is discussed. Further, new CTA techniques for radiation reduction are elaborated. Additionally, imagery for three cases of aortic endoleak detection using CTA and five cases using MRA are presented. Imaging for different types of endoleaks with CTA, MRA and CEUS are presented. For lifelong endoleak surveillance post-EVAR, CTA is still regarded as the imaging modality of choice. However, advancements in CEUS and MRA technique enable partial replacement of CTA in certain patients.
Gesehen am 21.02.2020